Determination of polychlorinated biphenyls in water by gas chromatography-electron capture detector combined with automated liquid-liquid extraction and dispersive solid phase extraction clean-up - HU Hongmei; GUO Yuanming; HAO Qing; SUN Xiumei; JIN Yanjian; ZHONG Zhi; ZHANG Xiaojun (浙江大学学报. 农业与生命科学版, 2016)
Polychlorinated biphenyls (PCBs) are a group of synthetic organic compounds and comprise a family of 209 possible congeners. PCBs are hazardous due to their persistence, hydrophobic character and toxic properties. Although they have been banned on a global scale since 1972, PCBs are still routinely found throughout the world and cause many ecotoxicological problems. Therefore, it is necessary to continue developing analytical methods for the analysis of PCBs in environmental samples. Analysis of PCBs in water is usually performed by gas chromatography (GC) or gas chromatography-mass spectrometry (GC-MS) combined with liquid-liquid extraction (LLE), solid phase extraction (SPE), solid phase disk extraction (SPDE), solid phase microextraction (SPME), headspace SPME (HS SPME), (magnetic) dispersive solid phase extraction (DSPE), dispersive liquid-liquid microextraction (DLLME) and membrane-assisted solvent extraction (MASE). Among these sample preparation methods, SPE, SPDE, SPME, and HS SPME usually suffer from high cost, sample carry-over, and time-declining performance. DLLME is easy to over-extraction and some matrix could be easily condensed. LLE as a reliable and simple method is often used for water sample pretreatment in large volumes. But after LLE, the extracts are usually required for further clean-up using concentrated sulfuric acid or SPE. (Magnetic) DSPE is quick, easy, cheap, effective, rugged and safe, but it is also subject to adsorbent. Besides, the extraction process is tedious, including dispersed, isolate, transfer, elute and even further purification. Therefore, the objective of this study was to develop an improved DSPE clean-up method to replace concentrated sulfuric acid or SPE after LLE, which needs less time and operation steps.Now, a simple, rapid, efficient, sensitive, and low matrix interference method for determination of seven PCBs (including PCB28, PCB52, PCB101, PCB118, PCB153, PCB138, PCB180) in water samples using gas chromatography-electron capture detector (GC-ECD) combined with automated LLE and DSPE has been described. In the designed experiment, water samples were firstly extracted with n-hexane, and then the extracts were directly purified by a suitable adsorbent. The kinds and amounts of adsorbent were optimized.Primary secondary amine (PSA) sorbent was chosen for DSPE purification, which could eliminate interferences to PCB28 and PCB52. But there were still some impurities to PCB52 and PCB28 by DSPE purification with C18 as sorbent as well as concentrated sulfuric acid purification. It may be because PSA could effectively remove carbohydrates, fatty acids, organic acids, polyphenols, sugar and polar pigments on the objective compounds, while C18 was mostly used to remove some non-polar disruptors such as fat and esters. By increasing the amount of PSA sorbent from 0 to 100 mg, the purify efficiency values increased significantly, and the recoveries of seven PCBs were almost invariant when the amount of sorbent ranged from 100 to 200 mg. As PSA could also adsorb n-hexane, increasing amount of PSA would result in a decrease of supernatant after centrifugation. Hence,100 mg PSA sorbent was used, at this point, good purify efficiency and satisfactory recoveries were both achieved. Furthermore, the present DSPE process only needed less than 5 min for dispersion and centrifugation.The linearity of this method ranged from 1.25 μg/L to 100 μg/L, with correlation coefficients ranging between 0.999 0 and 0.999 8. The detection limits for seven PCBs were 0.000 2-0.000 3 μg/L. The recoveries of spiked PCBs at different concentration levels in water samples of Qiandao Lake and seawater samples of Daiquyang sea area were 74%-105%, and 71%-107%, respectively, with relative standard deviations (RSDs) of 3.1%-6.2%, and 3.5%-5.9% (n=5), respectively. It was concluded that this method could be successfully applied for the determination of PCBs in water samples with good accuracy and precision.